Impact of establishing a Geriatrics Workforce Enhancement Program clinic on preventive health and Medicare Annual Wellness Visits - Huot, Charisse; Cruz-Knight, Wanda; Jester, Dylan J; Wenders, Anna; Andel, Ross; Hyer, Kathryn (Gerontology & geriatrics education, 2022)
We established a Geriatrics Workforce Enhancement Program (GWEP) clinic to enhance resident training on comprehensive preventive care and chronic disease management, and to increase the number of older patients who received Medicare Annual Wellness Visit (AWV) preventive services. A total of 1,104 patients were tracked at baseline and during the intervention period. Patients were grouped into two categories: Adult (aged 55-64) and Senior (aged 65+). Clinical quality measures were monitored by electronic health record and tracked through monthly reports at baseline (May 2018) and during the intervention period (July 2018-June 2019). In the Senior group, the proportion of patients receiving the Medicare AWV increased after GWEP began (p <.001). Additionally, the Senior group showed significant improvements in the frequency of body mass index assessments (p = .04), colorectal cancer screenings (p < .001), advance directive documentation (p < .001), cognitive screenings (p < .001), and pneumococcal vaccinations (p < .001). In the Adult group, a trending increase was seen in influenza vaccinations (p = .06). Curricular innovations including the establishment of a GWEP clinic in our residency outpatient center, development of new educational materials, and use of a nurse coordinator resulted in significant improvements in the percentage of older adults who received the Medicare AWV benefit and preventive health performance metrics.
Keywords: Workforce; preventative health; Geriatrics; služby preventivní péče; Preventive Health Services; Aged; geriatrie; Medicare annual wellness visit; Spojené státy americké; Humans; Medicare; senioři; lidé; United States; pracovní síly